Racing to disaster: A 10‐year retrospective analysis of pediatric competitive motocross injuries - Erin B. Bruney; Kalei M. Rollins; Carolyn K. Holland; Robyn Hoelle; David Martin; Colleen K. Gutman; Tricia Swan (Journal of the American College of Emergency Physicians Open)
Abstract Objectives In competitive motocross, children as young as 4 years old race in groups on motorized off‐road bikes on uneven terrain. We aimed to describe pediatric injuries occurring during an annual week‐long certified amateur motocross competition between 2011 and 2021. Secondarily, we compared injury characteristics and medical evaluation by age. Methods This retrospective analysis of injuries sustained by children during an annual motocross competition included children <18 years who received care for an event‐related injury within either of the two large regional hospital systems between 2011 and 2021. Data were collected through electronic health record review and analyzed with descriptive statistics. We used chi‐square and Fisher exact tests to compare findings by age (young child less than 12 years vs. adolescent 12 years or older). Results Over the 10‐week study period (1 week per year for each of 10 years), 286 encounters were made by 278 children. Nearly all children (280/286, 98%) underwent imaging; most had at least one traumatic finding (71.7% of x‐rays, 62.4% of computed tomography [CT] scans). Ninety‐three children (32.5% of 286) sustained multisystem injuries. Emergency department procedures included one endotracheal intubation, one thoracostomy, 46 closed reductions, and 37 procedural sedations. Twenty‐eight children (9.8% of 286) required operative intervention. Overall, 25.5% of children (73/286) were hospitalized and one adolescent died. Adolescents were more likely than young children to undergo CT imaging (40.1% vs. 26.8%, p = 0.042) and have multisystem injuries (36.3% vs. 23.2%, p = 0.045). There was no difference in hospitalization or operative intervention by age. Conclusion This comprehensive assessment of injuries sustained by children during competitive motocross demonstrates significant morbidity and mortality. Findings have implications for families who consider participation and health systems in regions where competitions occur.